2022
DOI: 10.7554/elife.73511
|View full text |Cite
|
Sign up to set email alerts
|

P2RY14 cAMP signaling regulates Schwann cell precursor self-renewal, proliferation, and nerve tumor initiation in a mouse model of neurofibromatosis

Abstract: Neurofibromatosis type 1 (NF1) is characterized by nerve tumors called neurofibromas, in which Schwann cells (SCs) show deregulated RAS signaling. NF1 is also implicated in regulation of cAMP. We identified the G-protein-coupled receptor (GPCR) P2ry14 in human neurofibromas, neurofibroma-derived SC precursors (SCPs), mature SCs, and mouse SCPs. Mouse Nf1-/- SCP self-renewal was reduced by genetic or pharmacological inhibition of P2ry14. In a mouse model of NF1, genetic deletion of P2ry14 rescued low cAMP signa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…The spots were examined under ultraviolet light at 254 nm and further visualized, where needed, by anisaldehyde or cerium ammonium molybdate stain solution. Column chromatography was performed on silica gel (40− (11). Pd/C (10%, 53 mg) was added to a solution of 31 (10.7 mg, 0.0177 mmol) in DMF (5 mL).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The spots were examined under ultraviolet light at 254 nm and further visualized, where needed, by anisaldehyde or cerium ammonium molybdate stain solution. Column chromatography was performed on silica gel (40− (11). Pd/C (10%, 53 mg) was added to a solution of 31 (10.7 mg, 0.0177 mmol) in DMF (5 mL).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, despite effectiveness, results with pNFs and first results using the Nf1 -KO model ( Prss56 Cre , Nf1 fl/fl ) (Coulpier et al, 2022) indicated that MEKi alone might not be a complete solution for mature cNFs, and the combination of MEKi with other agents emerged as a logical next step for cNF treatment. Neurofibromin plays a role in SCs and neurofibromas by regulating both the Ras/MAPK pathway (Kim et al, 1995; Sherman et al, 2000) and the cAMP pathway (Kim et al, 2001; Patritti-Cram et al, 2022; Serra et al, 2000). Both pathways need to be active for a prolific SC proliferation (Rahmatullah et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The role of neurofibromin in the cAMP pathway has also been determined (The, 1997; Tong et al, 2002) although much less understood at the molecular level. Recently, cAMP intracellular elevation has been involved in the reduction of SC precursor self-renewal and cNF SC proliferation (Patritti-Cram et al, 2022). In agreement, NF1 (+/-) and NF1 (-/-) cNF-derived SC cultures can be obtained basically by modifying the exposure to cAMP-elevating agents, since NF1 (-/-) SCs decrease proliferation after long expositions to elevated cAMP compared to NF1 (+/-) SCs (Serra et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Cell-type variations in DNA repair regulation by cAMP signaling after irradiation may be used to examine how cAMP signaling plays diverse roles in DNA repair [53]. Similarly, there may be a connection between the self-renewal of Schwann cell precursors and neurofibroma development through the purinergic receptor P2Y14 (P2RY14)/cAMP signaling pathway [54]. There are, however, several notable studies that concentrate on the function of cAMP in various cancer.…”
Section: The Camp-pka Pathway's Role In the Growth Of Various Tumorsmentioning
confidence: 99%